Effect of Spraying at Plant Collar and Adult Trapping on Banana Corm Weevil, Cosmopolites sordidus (Coleoptera: Cucurlionidae) - kueh tai, felicia fui (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The banana corm weevil, Cosmopolites sordidus (Coleoptera: Cucurlionidae) is the most concerned pest in all major banana and plantain growing countries. The first incident of C. sordidus was detected in Kpg. Remun, Gedung, Serian where 90% of the banana plants were infested. An on farm trial to evaluate the effect of chemical spraying at plant collar and trapping was carried out. Untreated plot served as the control. Only chemical spraying at the plant collar showed significant reduction of weevil damage to the plant. Nevertheless the percentage of damage was still high. It is concluded that no single treatment has effectively control this pest. With the introduction of integrated pest management (IPM) strategy which incorporates cultural and chemical controls, the pest infestation has been greatly reduced.